First dust study in JET with the ITER-like wall: sampling, analysis and classification. (15th October 2015) - Baron-Wiechec, A.; Fortuna-Zaleśna, E.; Grzonka, J.; Rubel, M.; Widdowson, A.; Ayres, C.; Coad, J. P.; Hardie, C.; Heinola, K.; Matthews, G. F.
Abstract: Results of the first dust survey in JET with the ITER-Like Wall (JET-ILW) are presented. The sampling was performed using adhesive stickers from the divertor tiles where the greatest material deposition was detected after the first JET-ILW campaign in 2011 – 2012. The emphasis was especially on sampling and analysis of metal particles (Be and W) with the aim to determine the composition, size, surface topography and internal dust structure using a large set of methods: high-resolution scanning and transmission electron microscopy, focused ion beam, electron diffraction and also wavelength and energy dispersive x-ray spectroscopy. The most important was the identification of beryllium dust both in the form of flakes and droplets with dimensions in the micrometer range. Tungsten, molybdenum, inconel constituents were identified along with many impurity species. The particles are categorised and the origin of the various constituents discussed.